Avaliacao da atividade da nova cefalosporina de quarta geracao cefpiroma contra amostras clinicas isoladas em unidades de terapia intensiva e unidades de oncoematologia de varios hospitais brasileiros - Mimiça, Igor; Segura, Adília; Sader, Hélio S.; Montelli, Augusto [UNESP]; Kesselring, Gustavo L. F.; Ribeiro, José E. F.; Mamizuka, Elza; Costa, Líbera; Sampaio, Jorge; Mendes, Caio M. F. (My University, 1996)
Objective: To evaluate the in vitro activity of the fourth-generation cephalosporin cefpirome in comparison to that of ceftazidime, ceftriaxone, cefotaxime and imipenem in a multicenter study involving nine hospitals from six cities (four states). Material and methods: A total of 804 isolates from patients hospitalized in either intensive care units or Oncology/Hematology units was evaluated. The isolates were collected between June and November of 1995, i.e. before cefpirome became commercially available in Brazil, and susceptibility tested by broth microdilution following the NCCLS procedures. All isolates resistant to cefpirome were retested by B-test. Results: Against Enterobacteriaceae (n = 344), cefpirome demonstrated an activity 2 to 32-fold higher than that of the third-generation cephalosporins (TGCs) and similar to that of imipenem. The percentages of Enterobacteriaceae susceptible were: 88%, 69% and 96% for cefpirome, TGCs and imipenem, respectively, The cefpirome spectrum were greater or equal to that of imipenem against Citrobacter freundii, Enterobacter aerogenes, Morganellao morganii and Serratia marcescens. Against Acinetobacter sp. (n = 77), cefpirome was slightly more active than ceftazidime; however, the percentages of isolates resistant to these compounds were high (84% and 88%, respectively). The activities of cefpirome, ceftazidime and imipenem were very similar against P. aeruginosa isolates (n = 128), with MIC50 (μg/ml) percent susceptible of 8/59%, 8/62% and 4/62% respectively, Against aerobic gram-positive bacteria, the cefpirome activity was 4 to 16-fold higher than that of TGCs but 2 to 8-fold lower than that of imipenem. Conclusion: The results of our study suggest that, in Brazil, cefpirome has a spectrum of activity which is higher than that of the TGCs against aerobic gram-negative (Enterobacteriaceae and non-Enterobacteriaceae) and gram-positive bacteria and similar to that of imipenem against some Enterobacteriaceae species and P. aeruginosa.
Antimicrobial activity of cefpirome compared to other broad-spectrum betalactam drugs against 804 clinical isolates from 9 Brazilian hospitals
Keywords: beta lactam antibiotic; cefotaxime; cefpirome; ceftazidime; ceftriaxone; cephalosporin; ciprofloxacin; gentamicin; imipenem; antibiotic sensitivity; antimicrobial activity; Citrobacter; Enterobacter; minimum inhibitory concentration; Morganella morganii; nonhuman; Pseudomonas aeruginosa; Serratia marcescens